Tagalog verb dictionary - Hawkins, Michael (Michael C.) (Northern Illinois University Press, 2011)
"A concise explanatory text and English-Tagalog/Tagalog-English verb guide designed to facilitate understanding and mastering the complex focal orientation of verbs in the Tagalog language"--